Financial Feasibility Analysis of Swallow Nest Business (Case Study of Mr. Rusdin's Business) in Lakawoghe Village, Kusambi District, West Muna Regency - Ahmad Aldin Bariuddin; Surni, Surni; Abdul Gafaruddin (International journal of technology and education research, 2024)
This study aims to determine the financial feasibility of swallow nest business in Lakawoghe Village, Kusambi Sub-district, West Muna Regency. This research was conducted in Lakawoghe Village, Kusambi District, West Muna Regency. This research took place from May 2023 until completion. The object of this research is Mr. Rusdin's swallow's nest business. This research uses a case study method with quantitative data analysis. This study aims to determine the feasibility of swallow's nest business in terms of financial aspects. Financial aspects were analyzed using the Net Present Value (NPV) method, Net B/C Ratio, Internal Rate of Return (IRR), Payback Period. The data used in this research are primary data and secondary data. The data collection techniques used are interviews and notes. The results showed that the NPV value was Rp.55,996,868. With the discount factor rate used is 10%, the Net B/C is 1.57, and the IRR value is 21.37%, and the Payback Period is 4.44 or for four years and four months